Enhancing Thermochemical Energy Storage Performance of Perovskite with Sodium Ion Incorporation - Zeyu Ning; Yibin He; Peiwang Zhu; Dong Chen; Fan Yang; Jinsong Zhou; Gang Xiao (Inorganics)
Perovskite materials are promising for thermochemical energy storage due to their ability to undergo redox cycling over a wide temperature range. Although BaCoO3 exhibits excellent air cycling properties, its heat storage capacity in air remains suboptimal. This study introduces Na into the lattice structure to enhance oxygen vacancy formation and mobility. DFT+U simulations of the surface structure of Na-doped BaCoO3−δ indicate that incorporating Na improves surface stability and facilitates the formation of surface oxygen vacancies. NaxBa1−xCoO3−δ compounds were synthesized using a modified sol–gel method, and their properties were investigated. The experimental results demonstrate that Na doping significantly enhances the redox activity of the material. The heat storage capacity increased by above 50%, with the Na0.0625Ba0.9375CoO3−δ solid solution achieving a heat storage density of up to 341.7 kJ/kg. XPS analysis reveals that Na doping increases the concentration of surface defect oxygen, leading to more active oxygen release sites at high temperatures. This enhancement in redox activity aligns with DFT predictions. During high-temperature cycling, the distribution of Na within the material becomes more uniform, and no performance degradation is observed after 300 cycles. Even after 450 cycles, Na0.0625Ba0.9375CoO3−δ retains over 96% of its initial redox activity, significantly outperforming fresh BaCoO3−δ. These findings elucidate the mechanism by which Na doping enhances the thermochemical heat storage performance of BaCoO3−δ and provide new insights for the design of perovskite-based materials.